The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.2170/jjphysiol.36.1193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of airway anaesthesia on the ventilatory and heart rate responses to isocapnic progressive hypoxia.

Abstract: The effect of airway anaesthesia by lidocaine inhalation on the hypoxic ventilatory response was examined together with the heart rate response by the isocapnic progressive hypoxia test in human subjects. During the test, end-tidal P~o2 (PETCo2) was maintained at the resting level. However, because resting PETCoz tends to decrease by airway anaesthesia, we conducted the test at the resting PETCo2 determined both before (normocapnic) and after lidocaine (hypocapnic). Ventilatory and heart rate response were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1990
1990
1990
1990

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
1
Order By: Relevance
“…They suggested that afferent vagal informa tion is required to elicit an increased rate of breathing in response to hypercapnia and hypoxemia. Little or no effect of airway anesthesia on the hypoxic venti latory and occlusion pressure responses in healthy subjects was reported by Tanaka et al [17] at our insti tute. Three possibilities may account for the discre pancy between those data and the results in this study.…”
Section: Responses To Hypoxiacontrasting
confidence: 70%
“…They suggested that afferent vagal informa tion is required to elicit an increased rate of breathing in response to hypercapnia and hypoxemia. Little or no effect of airway anesthesia on the hypoxic venti latory and occlusion pressure responses in healthy subjects was reported by Tanaka et al [17] at our insti tute. Three possibilities may account for the discre pancy between those data and the results in this study.…”
Section: Responses To Hypoxiacontrasting
confidence: 70%